Virtual Reality Exposure Therapy for Acrophobia: Designing a Game Application - Ardhi, Ovide Decroly Wisnu; Hidayat, Taufiqurrakhman Nur; Purnomo, Fendi Aji; Yudhanto, Yudho; Masbahah, Masbahah; Riatma, Darmawan Lahru; Hakimi, Nur Azizul; Hutabarat, Josua Arnatal (Universitas Sebelas Maret, 2022)
Abstract Anxiety disorders are the most common type of mental disorder Almost 18.1% of adults experience anxiety disorders, with the specific phobia subcategory being understudied. Studies indicate that the prevalence of specific phobias ranges from 3% to 15% worldwide, with phobias of heights and animals being the most common. While exposure therapy for anxiety disorders has strong evidence, not many therapists use this method. In this study, we employed an exposure therapy method that involved gradual and repeated exposure to a feared stimulus, resulting in changes in cognition, behavior, and emotional and physical responses. The study developed the exposure therapy method as Virtual Reality Exposure Therapy (VRET), utilizing an interactive and engaging 3D environment to facilitate new learning and provide an immersive experience for users. The research also leveraged VRET technology to assist in training, evaluating, delivering, and supervising psychotherapy skills. Our study resulted in a prototype of VRET that offers a more specific and detailed therapeutic tool for acrophobia in the form of game. The compatibility test results show that the iPhone XR 2021 and Poco X3 Pro 2021 can build applications 5 minutes faster than the Poco M3 2021 and 15 minutes from the Realme 3 2021. The Poco X3 Pro 2021 application installation process is 1 to 2 seconds faster than the iPhone XR 2021 and Poco M3 2021. Realme 3 2021 is 9 seconds slower than Poco X3 Pro 2021.Abstrak Gangguan kecemasan adalah jenis gangguan mental yang paling umum. Hampir 18,1% orang dewasa mengalami gangguan kecemasan, dengan subkategori fobia spesifik sedang dipelajari. Studi menunjukkan bahwa prevalensi fobia spesifik berkisar antara 3% hingga 15% di seluruh dunia, dengan fobia ketinggian dan hewan adalah yang paling umum. Sementara terapi pemaparan untuk gangguan kecemasan memiliki bukti kuat, tidak banyak terapis yang menggunakan metode ini. Dalam penelitian ini, kami menggunakan metode terapi pemaparan yang melibatkan pemaparan bertahap dan berulang terhadap stimulus yang ditakuti, menghasilkan perubahan dalam kognisi, perilaku, dan respons emosional dan fisik. Studi ini mengembangkan metode terapi pemaparan sebagai Virtual Reality Exposure Therapy (VRET), menggabungkan lingkungan 3D yang interaktif dan menarik untuk memfasilitasi pembelajaran baru dan memberikan pengalaman mendalam bagi pengguna. Penelitian ini juga memanfaatkan teknologi VRET untuk membantu melatih, mengevaluasi, menyampaikan, dan mengawasi keterampilan psikoterapi. Studi kami menghasilkan prototipe VRET yang menawarkan alat terapi yang lebih spesifik dan terperinci untuk akrofobia dalam bentuk permainan. Hasil uji kompatibilitas menunjukkan bahwa iPhone XR 2021 dan Poco X3 Pro 2021 dapat membangun aplikasi 5 menit lebih cepat dari Poco M3 2021 dan 15 menit dari Realme 3 2021. Proses instalasi aplikasi Poco X3 Pro 2021 lebih cepat 1 hingga 2 detik dibandingkan iPhone XR 2021 dan Poco M3 2021. Realme 3 2021 lebih lambat 9 detik dari Poco X3 Pro 2021.